Evaluation and improvement of promising rubber recycling OT machine using fractional factorial and response surface design. Issue 2 (3rd April 2019) - Elemary, Berihan R.
Abstract: A design of experiment (DOE) is used in many industrial sectors in the development and optimization of manufacturing processes. DOE is a more effective way to determine the impact of two or more factors on a response. In this paper, a Two-Level Fractional Factorial design was employed to develop the important factors that significantly affect new promising OT Rubber recycling machine using a DOEs analysis. Central composite design (CCD) and response surface methodology (RSM) were used to optimize the isolating screen size. The CCD considered five factors with two-level full factorial design. CCD experiments using RSM was proved to be an optimal tool for optimization.